Green Intellectual Capital on Firm Performance Moderated by Green Business Strategy in Craftsmanship SME’s - Eef Saifullah Doloan; Sabihaini Sabihaini; R Heru Kristanto HC (West Science Journal Economic and Entrepreneurship, 2024)
This study shows how SME’s performance is affected by the three components of green intellectual capital (GIC), namely green human capital (GHC), green structural capital (GSC), and green relational capital (GRC), and uses the moderating role of green business strategy (GBS) to explain the relationship. Data was collected from 92 SMEs in the craft industry in the Special Region of Yogyakarta. Primary data for the study was collected from respondents through closed-ended questionnaires distributed directly (offline) and google forms (online) to test the suggested model and analyzed using structural equation modeling with Smart PLS 3. The findings show that: 1) green intellectual capital has a negative influence on SME performance; 2) the three components of GIC have a positive influence on SME performance; 3) green business strategy weakens the influence of GIC on the performance of craft SMEs in Yogyakarta Special Region